Strong Ocean/Sea‐Ice Contrasts Observed in Satellite‐Derived Ice Crystal Number Concentrations in Arctic Ice Boundary‐Layer Clouds. Issue 13 (1st July 2022) - Papakonstantinou‐Presvelou, Iris; Sourdeval, Odran; Quaas, Johannes
Abstract: The Arctic climate changes at a faster rate than the rest of the globe. Boundary‐layer clouds may play an important role in this change. At temperatures below 0°C, mixed‐phase clouds exist and their phase and longevity is influenced by the abundance of ice crystals, which in turn is a function of aerosols serving as ice nucleating particles (INPs). Previous in situ studies suggested a local source of INPs due to biological activity over open ocean. Here we investigate ice crystal concentrations in clouds below 2 km at a large scale, by exploiting a newly developed data set—DARDAR‐Nice—retrieved from active satellite remote sensing. The data set spans from 2006 to 2016. Contrary to previous expectation, we find that at a given latitude and temperature, there are more ice crystals over sea ice than over open ocean. This enhancement is particularly found in clouds south of 70°N, and also at temperatures between 0°C and −10°C. Plain Language Summary: The Arctic region is particularly affected by climate change, its warming is 2–3 times larger than global average during recent decades. One of the contributors to this "Arctic Amplification" may be the Arctic clouds and in particular the mixed phase type, where ice and supercooled liquid coexist at temperatures lower than 0°C. Aerosols play a significant role in cloud formation, since without the presence of some effective particles, the ice crystals could not form at all at temperatures between 0°C and roughly −40°C. In this study, we use a new satellite data set which provides an important cloud quantity, the amount of ice crystals in the clouds. Although this data set is limited to pure ice clouds, it can prove useful for understanding the behavior of Arctic clouds. What we find here is that Arctic low‐level clouds show larger quantities of ice crystals over sea ice than over ocean and we think that this can be attributed to the amount and type of aerosols related to each surface. This finding contradicts a previous hypothesis, which stated that more ice crystals would possibly form over ocean because of the presence of highly ice effective aerosols there. Key Points: New ice microphysics from active satellite instruments enable large‐scale analysis of Arctic boundary‐layer clouds Ice crystal numbers are enhanced over sea ice compared to open ocean at temperatures above −10°C This difference is most pronounced in clouds south of 70°N through all the temperature range